Timeless tales of Beatrix Potter [compact disc, unabridged] Peter Rabbit and friends - Potter, Beatrix, 1866-1943 (Tantor Media, 2014)
Beatrix Potter's amazing universe of animals dressed in human clothing has taught and entertained children for over a century. Her love of animals and children is apparent in each of these twenty-one tales. The world of Beatrix Potter is as appealing now as when it was first created at the turn of the twentieth century.